Demographic Bonuses and Unemployement in Banten - Krisnando, Anselmus Marsvento Satrya; Syafitri, Wildan (Journal of Development Economic and Social Studies, 2026)
The demographic bonus, which will peak around 2030, places Banten Province in a critical position as its working-age population grows faster than its labor market capacity. This study analyzes the effects of the productive-age population, GRDP (constant prices), education level, and minimum wage on open unemployment across eight districts/cities in Banten from 2014 to 2024. A panel data regression using the Fixed Effect Model was applied following Chow and Hausman tests. The results show that productive-age population, GRDP, and education reduce unemployment, while minimum wage increases unemployment due to rising labor costs. These findings highlight the need for stronger labor absorption strategies to prevent the demographic bonus from turning into a demographic burden as 2030 approaches.